Analisis Pengaruh Likuiditas Terhadap Profitabilitas PT. BPD Maluku Malut (Persero) - Tentua, Julvana S.; Saptenno, Sammy; Fredriksz, Grace (Jurnal Administrasi Terapan, 2024)
BPD Maluku Malut (Persero), a regional government-owned enterprise operating in the banking sector, was established by the local government to increase regional revenue—a phenomenon observed at PT. BPD Maluku Malut (Persero) is that the ability to generate profit is inversely related to liquidity. Increased liquidity represents a cost of decreased profitability. This research aims to prove the influence of liquidity on profitability at PT empirically. BPD Maluku Malut (Persero). Using a quantitative approach, this study attempts to examine the influence of liquidity, represented by the Current Ratio and Quick Ratio, on profitability, represented by Return On Asset, at PT. BPD Maluku Malut (Persero). The data used is secondary data obtained from PT's financial statements. BPD Maluku Malut (Persero) for the period from 2013 to 2018. The method used in this research is multiple linear regression analysis. Based on the results of data analysis using the statistical method of multiple linear regression with the help of SPSS software, the Current Ratio has a significance value of 0.097, and the Quick Ratio has a significance value of 0.66. These results suggest that the Current Ratio and Quick Ratio do not significantly affect Return On assets Keywords: Liquidity, Profitability, Current Ratio, Quick Ratio and Return On Assets